2016
DOI: 10.1002/2016wr019362
|View full text |Cite
|
Sign up to set email alerts
|

The role of water treatment abstraction in the flux and greenhouse gas emissions from organic carbon and nitrogen within UK rivers

Abstract: The fate of organic matter through watersheds has been shown to be an important component of the global carbon cycle and processes in rivers can rapidly transfer carbon from the terrestrial biosphere to the atmosphere. However, the role of water abstraction in diverting organic matter from freshwater has not been considered. This study used two methods to estimate the amount of organic carbon removed by water treatment processes, first, by estimating the amount of carbon that has to be removed given the abstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…As shown by the previous studies of Finlay et al (), Noacco et al (), and Worrall et al (), the extensive monitoring records maintained in the United Kingdom over time and space mean that the United Kingdom is the ideal location for considering STWs as a source of DOC to rivers.…”
Section: Approach and Methodologymentioning
confidence: 88%
See 4 more Smart Citations
“…As shown by the previous studies of Finlay et al (), Noacco et al (), and Worrall et al (), the extensive monitoring records maintained in the United Kingdom over time and space mean that the United Kingdom is the ideal location for considering STWs as a source of DOC to rivers.…”
Section: Approach and Methodologymentioning
confidence: 88%
“…Worrall et al () attempted to correct the previous estimates of DOC flux and found the range 812 in 1,975 to 3,875 ktonnes C in 2004, that is, far higher than found here, but that study used the HMS data that contained the transcription error and also used data calibrated from water colour. Finlay et al (), when considering the fluvial flux of carbon from the United Kingdom, used a value of 904 ktonnes C/year for DOC flux at the tidal limit for the period 2005 to 2015 on the basis of values from Worrall et al () as updated in Worrall et al () but not using the same interpolation methods as in this study—this study would give the average annual DOC flux at the tidal limit for the period of 2005 to 2014 as 859 ktonnes C/year. Given the flux from STWs, it can be concluded that, at maximum, sewage effluent would comprise 3.6% of the DOC flux at the tidal limit of the United Kingdom.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations